Utilizing artificial intelligence and electroencephalography to assess expertise on a simulated neurosurgical task. (January 2023) - Natheir, Sharif; Christie, Sommer; Yilmaz, Recai; Winkler-Schwartz, Alexander; Bajunaid, Khalid; Sabbagh, Abdulrahman J.; Werthner, Penny; Fares, Jawad; Azarnoush, Hamed; Del Maestro, Rolando
Abstract: Virtual reality surgical simulators have facilitated surgical education by providing a safe training environment. Electroencephalography (EEG) has been employed to assess neuroelectric activity during surgical performance. Machine learning (ML) has been applied to analyze EEG data split into frequency bands. Although EEG is widely used in fields requiring expert performance, it has yet been used to classify surgical expertise. Thus, the goals of this study were to (a) develop an ML model to accurately differentiate skilled and less-skilled performance using EEG data recorded during a simulated surgery, (b) explore the relative importance of each EEG bandwidth to expertise, and (c) analyze differences in EEG band powers between skilled and less-skilled individuals. We hypothesized that EEG recordings during a virtual reality surgery task would accurately predict the expertise level of the participant. Twenty-one participants performed three simulated brain tumor resection procedures on the NeuroVR™ platform (CAE Healthcare, Montreal, Canada) while EEG data was recorded. Participants were divided into 2 groups. The skilled group was composed of five neurosurgeons and five senior neurosurgical residents (PGY4-6), and the less-skilled group was composed of six junior residents (PGY1-3) and five medical students. A total of 13 metrics from EEG frequency bands and ratios (e.g., alpha, theta/beta ratio) were generated. Seven ML model types were trained using EEG activity to differentiate between skilled and less-skilled groups. The artificial neural network achieved the highest testing accuracy of 100% (AUROC = 1.0). Model interpretation via Shapley analysis identified low alpha (8–10 Hz) as the most important metric for classifying expertise. Skilled surgeons displayed higher (p = 0.044) low-alpha than the less-skilled group. Furthermore, skilled surgeons displayed significantly lower TBR (p = 0.048) and significantly higher beta (13–30 Hz, p = 0.049), beta 1 (15–18 Hz, p = 0.014), and beta 2 (19–22 Hz, p = 0.015), thus establishing these metrics as important markers of expertise. ACGME Core Competencies: Practice-Based Learning and Improvement. Highlights: The Artificial Neural Network (ANN) model is the best surgical expertise classifier. Low alpha (8–10 Hz) is the most predictive EEG metric of surgical expertise. It is possible to predict surgical expertise with 100% accuracy using only EEG data. Skilled surgeons operate with higher overall Beta, Beta 1, Beta 2, and Low alpha. Skilled surgeons operate with a lower theta/beta ratio.